SUBJECT MATTER OF SECURITY SOCIOLOGY INSTANCE OF CRITICAL SOCIOLOGY - Rossa, Jerzy (Studia Administracji i Bezpieczeństwa, 2023)
In the essay Im looking for a subject matter of sociological research concepts formation strategies in sociological works of Vida Bajc from The University of Yale. Ms. Bajc analysis of modern security apparatus follows such paths of critical sociology of security which takes especially bureaucratic methods of absolute security production into account. Special research subjects of Ms. Bajc are techniques of public spaces creation and control. Cognition of secu-rity according to Vida Bajc is anchored in patterns of European culture indi-vidualism. In such frames of reference asserts itself real and symbolic segmen-tation of society in contradistinction to oriental holistic culture and its ac-ceptance of ritual insecurity. In my commentary of critical sociology of Ms. Bajc Im searching for a web of sociological concepts which delineate sociol-ogy of security research subject.